Leading Bank Performances under Exntended Caretaker Goverment- Empirical Approach from Thailand - Debkumar, Chatterji Sudip (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
Thailand’s economic performance has historically been determined by the frequency and severity of political de-stability by government collapses mostly organized through army coups. This study investigated the theoretical and empirical literature political uncertainty and economic slowdown arising out of the last coup and caretaker government enforcing the emergency decree to maintain peace and order and the caretaker government being in power until the general elections were held in 2019. This paper scrutinizes the impact of political instability, macroeconomic and bank-specific factors on the performance of leading Thai banks in the context of Thailand. The study selected only two out of top 4 private banks due to the availability of data for the uncertainty period ranging from 2014 to 2018 until elections were held a year later. The study used 8 common measures of bank performance and profitability along with descriptive analyses. Using happiness index as qualitative standpoint and also comparing financial variables with rating agencies prediction, various reports including the Bank of Thailand, the study also presents some new results and a robustness analysis. Our study concludes that political uncertainty was a significant contributor for erratic bank performance.